2020
DOI: 10.12928/pharmaciana.v10i1.12318
|View full text |Cite
|
Sign up to set email alerts
|

The gastroprotective effects of arrowroot tuber starch (Maranta arundinacea L.) on ethanol-induced gastric damages in rats

Abstract: Empirically, arrowroot tubers (Maranta arundinacea L.) have been widely used in the treatment of gastric ulcers. They are known to contain carbohydrates and flavonoids that play a role in reducing inflammation. This study sought to identify the gastroprotective effects of arrowroot tuber starch (Maranta arundinacea L.) on the ulcer index, % protection ratio, and the histopathological image of Wistar rat models of gastric ulcers. The test animals were divided into six groups. Group I was given free access to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Jenang garut biasa dikonsumsi masyarakat setempat untuk meredakan sakit perut yang diakibatkan asam lambung (Hasil wawancara: Prihatin, 2024). Hal ini sejalan dengan penelitian Lailli et al (2020) yang menyebutkan bahwa kandungan polisakarida dalam umbi garut dipercaya dapat berikatan dengan area mukosa lambung sehingga mampu meningkatkan kemampuan pati garut dalam membentuk lapisan pelindung pada dindinglambung.…”
Section: Keberagaman Wild Edible Plants Jenis Umbiumbianunclassified
“…Jenang garut biasa dikonsumsi masyarakat setempat untuk meredakan sakit perut yang diakibatkan asam lambung (Hasil wawancara: Prihatin, 2024). Hal ini sejalan dengan penelitian Lailli et al (2020) yang menyebutkan bahwa kandungan polisakarida dalam umbi garut dipercaya dapat berikatan dengan area mukosa lambung sehingga mampu meningkatkan kemampuan pati garut dalam membentuk lapisan pelindung pada dindinglambung.…”
Section: Keberagaman Wild Edible Plants Jenis Umbiumbianunclassified
“…The arrowroot starches have potential medicinal properties, such as the treatment of gastric ulcers and the protection of the gastrointestinal tract. Damarwati et al (2020) indicated that arrowroot tuber starch could improve rat stomachs after the ulcer induction [ 1 ]. Meanwhile, Gutierrez et al (2018) suggested that arrowroot starches had a low in vitro digestibility rate, which was beneficial for people suffering from obesity and diabetes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rheological properties of starch gels, such as thixotropism, viscoelasticity, solidification rate and temperature response during extrusion, are the most important parameters associated with the accuracy and shelf life of 3D printed products [ 15 , 16 ]. However, the above-mentioned rheological properties of arrowroot starch gels have not been fully investigated before [ 1 ].…”
Section: Introductionmentioning
confidence: 99%